Influence of fuel moisture content and reactor temperature on the calorific value of Syngas resulted from gasification of oil palm fronds - Atnaw, S.M. (2014)
Biomass wastes produced from oil palm mills and plantations include empty fruit bunches (EFBs), shells, fibers, trunks, and oil palm fronds (OPF). EFBs and shells are partially utilized as boiler fuel while the rest of the biomass materials like OPF have not been utilized for energy generation. No previous study has been reported on gasification of oil palm fronds (OPF) biomass for the production of fuel gas. In this paper, the effect of moisture content of fuel and reactor temperature on downdraft gasification of OPF was experimentally investigated using a lab scale gasifier of capacity 50 kW. In addition, results obtained from equilibrium model of gasification that was developed for facilitating the prediction of syngas composition are compared with experimental data. Comparison of simulation results for predicting calorific value of syngas with the experimental results showed a satisfactory agreement with a mean error of 0.1 MJ/Nm3. For a biomass moisture content of 29, the resulting calorific value for the syngas was found to be only 2.63 MJ/Nm3, as compared to nearly double (4.95 MJ/Nm3) for biomass moisture content of 22. A calorific value as high as 5.57 MJ/Nm3 was recorded for higher oxidation zone temperature values. Â© 2014 Samson Mekbib Atnaw et al.